Förster resonance energy transfer and improved charge mobility for high performance and low-cost ternary polymer solar cells. (1st September 2019) - Liu, Desheng; Fan, Pu; Zhang, Dayong; Zhang, Xiaohua; Yu, Junsheng
Highlights: α-6T as an electron donor is firstly introduced to fabricate a low-cost TPSC. Obvious improvement of PCE with an increase of JSC and FF is achieved. Performance improvement is mainly due to the FRET and enhanced charge mobility. α-6T decreases the resistance and provide more pathways for charge transportation. α-6T can also modulate the morphology of the active layer. Abstract: In this study, the enhanced performance of a conventional bulk heterojunction (BHJ) system based on poly(4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl) (PTB7):[6, 6]-phenyl C71-butyric acid methyl ester (PC71 BM) is realized by adding a high charge mobility and low-cost small-molecular material of alpha-hexathienyl (α-6T) as an electron donor. Both the short circuit current ( JSC ) and fill factor (FF) are facilitated by adding 2 wt% α-6T to form a ternary system, resulting in a 22.2% improvement of power conversion efficiency (PCE) compared with the control binary device. The state-of-art BHJ layer was characterized by UV–Vis absorption, steady-state photoluminescence, space-charge-limited current, atomic force microscopy, and impedance spectra, and the enhanced device performance is mainly attributed to the Förster resonance energy transfer effect from α-6T to PTB7 and the increased charge mobility. The result also showed that the blend morphology can be modulated by the introduction of α-6T electron donor. Moreover, the incorporation of α-6T can contribute to the formation of more potential pathways for charge transportation in the active layer, and decrease the resistance of device.